Synthesis of Core–Shell Polyborosiloxanes as a Heat-Resistant Platform - Gunes, Deniz; Karagoz, Bunyamin (American Chemical Society (ACS), 2022)
Herein, new polyborosiloxanes (PBSs) were prepared using a straightforward synthetic approach to obtain a core-shell structure as a material with various features such as better adhesion ability to the applied surface and enhanced thermal properties. In this concept, in situ core-shell formation was allowed by sequential addition of ingredients with fixed conversions. First, pre-condensed polysiloxane was synthesized, with a 60% conversion, as a core by the reaction of phenyltriethoxysilane in the presence of water in an acidic condition. Subsequent addition of boric acid into the pre-condensate and a further condensation reaction resulted in the formation of the shell layer through the introduction of the -Si-O-B- bonds to the network of the PBS. The resulting resin was used as a binder for heat-resistant paint in combination with an aluminum pigment, and the paint applied on a metal plate was found to be resistant up to 600 °C in terms of adhesion strength. It was also demonstrated that the incorporation of boron in the core-shell structure showed better adhesion strength than the one-pot preparation of PBS. Using this method, not only the heat resistance requirement of the industrial coating was achieved but also the flame-retardant ability was introduced.
Keywords: Chemistry; QD1-999